2017
DOI: 10.1016/j.onehlt.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The first report of Escherichia fergusonii isolated from non-human primates, in Africa

Abstract: The aim of this study was to determine the resistance phenotypes of selected enteric bacteria isolated from non-human primates at a wildlife-human interface. Bacterial isolates from faecal samples of non-human primates at two wildlife rehabilitation centres in South Africa were screened for the presence of Escherichia coli. The biochemical characterisation of E. coli and E. coli-like bacteria revealed both adonitol positive and sorbitol negative strains – a unique characteristic of Escherichia fergusonii and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 32 publications
2
30
0
1
Order By: Relevance
“…Multidrug-resistant Extraintestinal pathogenic E. coli (ExPEC) clones have contributed significantly to the growing antibiotics resistance burden [1,2]. Several clinical multidrug-resistant ExPEC clones, including ST131, ST73 and ST40, reported in previous studies, have acquired resistance plasmids that encode multiple beta-lactamase genes, particularly those required for Extended-spectrum beta-lactamase (ESBL) production [3][4][5][6][7]. This facilitates their capacity in playing significant roles in the global dissemination of ESBL genes [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multidrug-resistant Extraintestinal pathogenic E. coli (ExPEC) clones have contributed significantly to the growing antibiotics resistance burden [1,2]. Several clinical multidrug-resistant ExPEC clones, including ST131, ST73 and ST40, reported in previous studies, have acquired resistance plasmids that encode multiple beta-lactamase genes, particularly those required for Extended-spectrum beta-lactamase (ESBL) production [3][4][5][6][7]. This facilitates their capacity in playing significant roles in the global dissemination of ESBL genes [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Another extraintestinal human pathogen within the genus Escherichia has also shown tendencies for the dissemination of plasmid-mediated beta-lactamase genes. Escherichia fergusonii closely related to the ExPECs with about 60% similarity, was classified in 1985 as a new specie [7]. Escherichia fergusonii are opportunistic pathogens primarily associated with abdominal wounds, UTIs and bacteraemia in humans while causing septicaemia and diarrhoea in animals [7,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another case in Canada, a goat developed chronic diarrhea and became emaciated, and E. fergusonii was isolated from the feces and several internal organs, namely, kidney, lung, liver and intestine (Hariharan et al (2007). Recently, in an investigation of non-human primates in Africa, Glover et al (2017) identified E. fergusonii as a possible emerging pathogen of zoonotic importance.…”
Section: Introductionmentioning
confidence: 99%
“…O f the eight Escherichia species (1, 2), E. fergusonii and E. coli are easily confused during isolation due to their phenotypic and genotypic similarities (1,3). E. fergusonii is pathogenic to both humans and animals (1,3,4,5,6) and has reportedly acquired multiple-drug resistance (1,6). Since there is limited research on antimicrobial resistance in E. fergusonii, an isolate from chicken feces from Zhejiang Province, China, was examined for antimicrobial resistance.…”
mentioning
confidence: 99%